Perceived styles of leaders of commission-based employees in an insurance company in South Africa. - Arthur, Douglas Vivian (My University, 2016)
The current study was conducted to examine the perceived leadership style of leaders of commissioned based employees in the long term insurance industry in South Africa. Specifically, it probes transactional and transformational leadership styles and employees’ perception of these types of leadership. To establish to what extent employees have a common perception of leadership, employees were segmented on the basis of age, gender, tenure and educational qualification. Managers or leaders of the employees, who were also invited to participate, provided their own assessment of their management style. This provided a valuable benchmark in the study. Considering the highly regulated industry in which these employees operate, a bias towards transactional leadership was anticipated. However with the requirements for mature, highly educated and trained employees, a bias for transformational leadership was also anticipated. The overall results however showed that although there was a good balance between transactional and transformational leadership, the scale tipped, marginally, in favour of transformational leadership. When considering age and gender, no significant difference in employees perception of leadership was observed. When considering tenure, a significant difference in tenure bands was observed – transactional leadership was seen to be prevalent for employees who were in their role for less than 2 years. Startling that transactional leadership was also observed for employees who were in their role for longer than 5 years. Transformational leadership dominated the group between 2 -5 years of service. The results also showed that employees with a post matric qualification perceived their leaders to be more transformational than transactional. Differences between leaders view of their leadership style and employees perceptions to high light the most significant gaps is also presented in the report.
MBA
Keywords: Leadership -- South Africa. Insurance companies -- South Africa -- Management.